2016
DOI: 10.1007/s10704-016-0082-1
|View full text |Cite
|
Sign up to set email alerts
|

On the choice of parameters in the phase field method for simulating crack initiation with experimental validation

Abstract: International audienceThe phase field method is a versatile simulation framework for studying initiation and propagation of complex crack networks without dependence to the finite element mesh. In this paper, we discuss the influence of parameters in the method and provide experimental validations of crack initiation and propagation in plaster specimens. More specifically, we show by theoretical and experimental analyses that the regularization length should be interpreted as a material parameter, and identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 172 publications
(101 citation statements)
references
References 40 publications
9
92
0
Order By: Relevance
“…We again observe very complex micro cracking patterns, but the morphology is different from the tensile test: in this case, the microcracks are roughly aligned with the direction of the load, while in the tensile test they propagate in direction perpendicular to the load. This is in agreement with other observations in more simple heterogeneous quasi-brittle samples [19].…”
Section: Resultssupporting
confidence: 94%
“…We again observe very complex micro cracking patterns, but the morphology is different from the tensile test: in this case, the microcracks are roughly aligned with the direction of the load, while in the tensile test they propagate in direction perpendicular to the load. This is in agreement with other observations in more simple heterogeneous quasi-brittle samples [19].…”
Section: Resultssupporting
confidence: 94%
“…This explains that the obtained g c (1.8 N/m) is larger than the one measured in the previous study of Romani et al (2015) of about 1.4 N/m. The increased strength may also induce a larger critical stress s c , which is associated with a smaller process zone length ℓ, (according to the analysis in Nguyen et al, 2016a). Indeed ℓ was found to be 0.1 mm in Romani (2013) and is now identified to be four times smaller.…”
Section: Identification Of Materials Parameters G C and ℓ By Inverse Amentioning
confidence: 92%
“…It has been shown (see e.g Nguyen et al, 2016a;Amor et al, 2009;Kuhn et al, 2015;Benallal and Marigo, 2007) that ℓ is related to other material parameters and then should be identified experimentally as such. In Section 4, we conduct such identification by inverse analysis coupling simulation and experiments.…”
Section: Phase Field Model Of Regularized Brittle Fracturementioning
confidence: 99%
See 1 more Smart Citation
“…In the second case, l should be identified from experimental data. Such analysis with experimental validations has been recently published in Nguyen et al (2016). It is demonstrated that this kind of regularized model converge to the brittle failure theory when l vanishes.…”
Section: Phase Field Modeling Of Stress Corrosion Crackingmentioning
confidence: 80%